Spatial distribution of Elasmobranchs on the Ecuadorian continental coast - Moreno, Ana (2018)
For centuries, fishermen have practiced shark fishing in the coastal waters of Ecuador; although little information is available on catches and species status. The present research aimed to determine, through the calculation of ecological wealth, the species distributed in an area that covers from the north of Manta in the province of Manabí (00059.92’S - 80053.93’W) to the southern border of Ecuador (03º23.10’S - 80027.60’W) and the spatial relationship between catches, by oceanographic cruisers from November 1994 to July 1999, using networks of drag shrimp trawlers on a course of three depths; stratum I (10 to 30 m), II (31 to 80 m) and III (81 to 200 m); whose purpose was to determine the variables of catch volumes and the incidence of trawl nets as one of the major environmental problems that can affect the structure and functioning of marine systems and their populations at the community and ecosystem levels, aggravated by non-compliance with control and management measures. In terms of fishing volumes by strata, the Gulf of Guayaquil, was the site with the highest number of species collected by exploration cruisers. These data will serve as a basis for the elaboration and support of the national shark management and conservation plan for Ecuadorian waters.